PHONOLOGICAL DIMENSION OF THE ARABIC WORDS: THE INTIMATE RELATION BETWEEN SOUND AND MEANING IN THE ARABIC WORDS - Khitam, Achmad Khusnul (Arabi : Journal of Arabic Studies, 2019)
This research aims to discover the relation between sound and meaning in the Arabic words. Sound, as the smallest contrastive linguistic unit has a huge influence on bringing change of meaning. The preference of certain phoneme on a word may produce certain meaning inside it. Therefore, a singel word with different phonemes produces different meaning. This research based on library research, a research proceed by gathering some facts from various books, articles, and other literatures related to the subject. This research combines semantical approach and phonological approach with analytic description method. From this research, it is found that Arabic words use certain phoneme to express certain meaning; phoneme with heavy articulation oftenly uses to express heavy activity, and phonems with light articulation oftenly uses to express light acivity.